2021
DOI: 10.3389/fgene.2021.745715
|View full text |Cite
|
Sign up to set email alerts
|

A Competitive Endogenous RNA Network Based on Differentially Expressed lncRNA in Lipopolysaccharide‐Induced Acute Lung Injury in Mice

Abstract: Non-coding RNAs have remarkable roles in acute lung injury (ALI) initiation. Nevertheless, the significance of long non-coding RNAs (lncRNAs) in ALI is still unknown. Herein, we purposed to identify potential key genes in ALI and create a competitive endogenous RNA (ceRNA) modulatory network to uncover possible molecular mechanisms that affect lung injury. We generated a lipopolysaccharide-triggered ALI mouse model, whose lung tissue was subjected to RNA sequencing, and then we conducted bioinformatics analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 87 publications
(102 reference statements)
0
4
0
Order By: Relevance
“…Among the screened lncRNAs, the study identified five different lncRNAs (LNC_006493, RP23-462P13.1, RP23-36001.1, RP24-150D8.2, and RP24-79P8.1) that have critical roles in ALI. These lncRNAs can downregulate Nkx2-1 and act as ceRNAs for the overexpressed mmu-miR-135b-3p [ 122 ].…”
Section: Lncrnas In Ali/ardsmentioning
confidence: 99%
“…Among the screened lncRNAs, the study identified five different lncRNAs (LNC_006493, RP23-462P13.1, RP23-36001.1, RP24-150D8.2, and RP24-79P8.1) that have critical roles in ALI. These lncRNAs can downregulate Nkx2-1 and act as ceRNAs for the overexpressed mmu-miR-135b-3p [ 122 ].…”
Section: Lncrnas In Ali/ardsmentioning
confidence: 99%
“…GAS5 is downregulated in childhood pneumonia, acute lung injury, and asthma, and its overexpression can cause the inhibition of in ammation and epithelial cell apoptosis [17][18][19] . In our previous genomic study on lipopolysaccharideinduced acute lung injury, the expression of GAS5 was signi cantly altered [20] , but its expression pattern in BPD was unclear. Through a bioinformatics analysis, we found several microRNAs (miRNAs) that coexisted with GAS5 and Sox9, which may constitute a competing endogenous RNA regulatory pathway.…”
Section: Introductionmentioning
confidence: 97%
“…These differentially expressed miRs can exacerbate or mitigate BPD progression (12)(13). A research team also found differential expression of miR-195-5p in the lung tissue of a mouse model of lipopolysaccharide-induced acute lung injury (14). Therefore, it is valuable to study the potential role of miR-195-5p in BPD development.…”
Section: Introductionmentioning
confidence: 99%